Álvaro de Luna, Juan Pacheco y Beltrán de la Cueva: un estudio comparativo del privado regio a fines de la Edad Media - Carceller Cerviño, María del Pilar (En la España Medieval, 2009)
Álvaro de Luna, Juan Pacheco and Beltrán de la Cueva were the protagonists of the conflictive reigns of Juan II and Enrique IV; all of them distinguished as royal favorites or privados. Historical circumstances and the evolution of the monarchy lent these privanzas similar characteristics, although their development also proved very different, until the figure of the privado disappeared with the advent of the Catholic Monarchs.
Keywords: Álvaro de Luna; Juan Pacheco; Beltrán de la Cueva; John II of Castile; Castile Fifteenth century; Favorites